Hak Subpoena sebagai Instrumen Pendukung Pelaksanaan Fungsi Dewan Perwakilan Rakyat - . Zamrony (Universitas Bandar Lampung (UBL), 2011)
Rights of the house of representatives to present and give information to someone byforce (subpoena rights), accompanied by sanctions hostage is controversial. On oneside, the autorities forcibly required for the functions of the House to run well. Buton other side, the force is potential to create uncertainty due to the arbitrariness ofits implementation mechanisms. Parliament is not a law enforcement agency but apolitical institution. Ideally, the sactions also held political sactions. Moreover,subpoena rights design owned by Parliament can be used in every implementationthe functions. Initially, the right to subpoena can only be used in the implementationof inquiry as the most special rights owned by the House of Representatives. But now,in legislation the right to subpoena expanded scope. The implication, in every forumsession, the Parliament has the ultimate weapon that make it as a superior institution.